Topology-Aware, Performance-Driven Adaptive Routing in Software-Defined Networks Using Dual-Agent Reinforcement Learning - Goteti, Deepthi; Reddy, Vurrury Krishna (Informatica, 2025)
This research explores adaptive routing in Software-Defined Networks (SDNs) using reinforcement learning. Two models—R-Learner (Q-learning) and R-Optimizer (policy-gradient)—are evaluated against the Dijkstra baseline across four topologies: Fat Tree, Abilene, Custom, and Dense Adaptive Mesh. Experiments run over 100 TCP/UDP traffic episodes using Mininet and the Ryu controller. Key metrics include throughput, jitter, round-trip time (RTT), and packet loss ratio (PLR). Statistically validated results show R-Optimizer outperforms R-Learner, achieving 7.4% higher throughput, 44% lower jitter, 19.5% lower RTT, and >50% lower packet loss. Both models also surpass Dijkstra in throughput and delay reduction. These results support reinforcement learning as a viable approach for real-time SDN routing and future controller integration.